1997
DOI: 10.1046/j.1469-8137.1997.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of fructans following oxygen deficiency stress in related plant species with different flooding tolerances

Abstract: SUMMARYIn the present work we compare responses to hypoxia of the carbohydrate content of related plant species, which grow naturally on sites prone to flooding {Senecio aquaticus Hill., Myosotispalustris (L.) Lehm. Rchb.) with plants from habitats with only a low risk of oxygen shortage (Senecio jacobaea L., Myosotis arvensis (L.) Hill.). Whilst the amounts of glucose, fructose and sucrose changed only slightly following hypoxia and peaked at a maximum approximately double that of the aerated control specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The physiological roles for cell wall thickenings are not clear, their function as a barrier for apoplastic movement is uncertain, and most arguments suggest mechanical reinforcement of the root tissue (Degenhardt and Gimmler 2000). Reduced sink activity is reflected by the strong retardation of growth in the root system (50% of control; Albrecht et al 1997). The increased cellulose content in the stele and exodermis adds mechanical support within root structures and may compensate for the progressive dissolution of cortical cells during aerenchyma formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological roles for cell wall thickenings are not clear, their function as a barrier for apoplastic movement is uncertain, and most arguments suggest mechanical reinforcement of the root tissue (Degenhardt and Gimmler 2000). Reduced sink activity is reflected by the strong retardation of growth in the root system (50% of control; Albrecht et al 1997). The increased cellulose content in the stele and exodermis adds mechanical support within root structures and may compensate for the progressive dissolution of cortical cells during aerenchyma formation.…”
Section: Discussionmentioning
confidence: 99%
“…In many grasses and dicots subjected to hypoxia Suc is converted into fructans, which are stored in the vacuole (Albrecht et al 1997;Albrecht and Biemelt 1998). In many grasses and dicots subjected to hypoxia Suc is converted into fructans, which are stored in the vacuole (Albrecht et al 1997;Albrecht and Biemelt 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has demonstrated that pre‐stress stored carbohydrate content is positively correlated with improved survival under flooding conditions. That has been attributed not only to their positive effects on maintenance of anaerobic respiration (Albrecht, Biemelt, & Baumgarten, ; Vriezen, Zhou, & van der Straeten, ) under flooding conditions but also due to their ability to recover after the end of stress (He, Patick Bentley, & Scott Holaday, ). For example, the high flood tolerance of Phalaris arundinacea , a known invasive grass species, has been ascribed to its high content of fructose polymers in its rhizomes (Tamura & Moriyama, ) as well as its more efficient use of carbohydrates under flooding conditions (Qin, Li, Chen, & Xie, ).…”
Section: Effects Of Flooding On Cool‐season Grass Metabolismmentioning
confidence: 99%
“…Other reports include the effects of drought stress (Pilon‐Smits et al. , 1995), hypoxia (Albrecht et al. , 1993, 1997), carbon dioxide (Smart et al.…”
Section: Introductionmentioning
confidence: 99%